239 Relationship Between Body Temperature and Behavior-Activities of Non-Pregnant Early Lactation Dairy Cows. (12th April 2022) - Brunton, Mercedes E; Montes, Maria Elisa; Mann, Adrianna; Teeple, Kelsey; George, Uduak; Boerman, Jaquelyn P; Casey, Theresa
Abstract: Animal behavior is a component of animal welfare and known to affect physiology as a primary input to the circadian system. Our objectives were to determine if non-pregnant, early lactation dairy cows in a free-stall exhibited circadian rhythms of behavior and core body temperature, and if oscillations in daily behaviors and activities of a cow relate to daily oscillations in body temperature or estrus, parity, and days in milk (DIM). Thirty Holstein cows (21-80 DIM) were observed for a 48-h period. The activities of standing, eating, ruminating, lying, and estrus behavior were recorded every 10 min. Data loggers (ibuttons) secured to blank (progesterone removed) controlled internal drug release (CIDR) devices were placed intravaginally in a subset of cows (n = 11) to record body temperature every 10 min over the same 48 h period. Cows were milked twice each day starting approximately 05:00 and 17:00, and the 70 min period encompassed moving cows to and from the milking parlor. The entire period cows were away from the free-stall was marked as milking. An ethogram was created using a binary system (0, 1), with 1 for each behavior. Behavior and temperature data were graphed for visualization, and cosine fit analysis found lack of evidence for circadian rhythms. Programs in R were used to plot behavior to overlay temperature recordings over the 48 h period to determine if temperature varied with behavior-activity. Temperature increased during milking periods in 8 of 11 cows (statistical method in development), but no other relationships were found. To study patterns of behavior, an adjacency matrix was utilized to create a directed graph for each cow. Analysis of the effect of estrus, parity and DIM on behavior patterns is ongoing. Computational approaches are currently being developed that may serve as tools to analyze the effect of production management systems on cow behavior.